Future of Rohingyas: Dignified Return to Myanmar or Restoring Their Rights or Both - Md. Mahbubur Rahman; Haradhan Kumar Mohajan; Tripty Kana Bose (Center for Southeast Asian Social Studies (CESASS), 2021)
At present Bangladesh is hosting more than 1.1 millions of Rohingyas who have been migrated from Myanmar and maximum of them are living in 34 makeshift camps of Cox’s Bazar and some thousands start to live at Bhashan Char of Bangladesh. The Government of Bangladesh (GoB) does not recognize Rohingyas as refugees and so they are not entitled to claim even the rights of refugees in Bangladesh. Getting support from the international community, the GoB still tries to repatriate Rohingyas to Myanmar, as the repatriation will relieve the huge burden of Bangladesh. But Rohingyas are not interested to go back to their home country, Myanmar, without establishing their citizenship and some other rights. As a result, till today not a single Rohingya has been repatriated to Myanmar and so at present the future of the Rohingya is in uncertainty. Bangladesh always think the fruitful solution of the Rohingya Crisis lies on their repatriation but more than three years after Rohingyas’ new entry in 2017 no repatriation happens and so the question arises. “What may be the future of Rohingyas?”, “Is the future of Rohingyas rely on their repatriation or staying in Bangladesh for a longer period of time with or without restoring their rights?”, would be tried to discuss in this article. If the Rohingyas will have to stay in Bangladesh for a longer time, then what the GoB should do, will also be discussed in this paper. For this, the field visit and interviews with Rohingya refugees at Rohingya Refugee Camp in 2018 and also in 2020 by the first author, M. M. Rahman, and his more than 3 years working experience on Rohingya crisis at BTV (Bangladesh Television) and the literature reviews by all the authors will be utilized.